The Diction’s Use and Public Understanding of Asmarandana Song by Raden Ngabei Yasadipura - Insiyah, Siti Johar; Sofyan, Akhmad (Interdisciplinary Social Studies, 2022)
The song Asmarandana was created by Raden Ngabei Yasadipura whose diction comes from the Javanese language so that it cannot be directly understood by the general public. The purpose of this study was to reveal the use of diction, rhyme, meaning, and to find out the public's response to the song. The method used in this research is descriptive qualitative method. Data collection was carried out using library and interview techniques. The research results are as follows. The diction uses the Javanese language which is adapted to the rhyme with other dictions in one line and stanzas. The rhyme of the Asmarandana song is that there are seven lines in each gatra, the wilangan is 8-8-8-8-7-8-8, and the song is i-a-e-a-a-u. As for the meaning of the Asmarandana song, namely: every human being who will undergo a marriage should not only look at looks and wealth but look at the heart and character for happiness that is sakinah mawaddah warahmah. The public's response to the song is divided into three, namely: the Santri community, Javanese, and modern. The santri community interprets the Asmarandana song as a form of reasoning in the letter Ar-rum verse 21 that humans are created in pairs. The Javanese people interpret the Asmarandana song as being associated with the terms seed, bebet, and weight. Modern society is generally no longer familiar with the Asmarandana song, but most of them in looking for a life partner are still guided by the requirements contained in the Asmarandana song.